2019
DOI: 10.3390/medicina55060297
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of HIV-1 Replication in MACROPHAGES is Led by Co-Receptor Usage

Abstract: Background and objectives: To enter the target cell, HIV-1 binds not only CD4 but also a co-receptor β-chemokine receptor 5 (CCR5) or α chemokine receptor 4 (CXCR4). Limited information is available on the impact of co-receptor usage on HIV-1 replication in monocyte-derived macrophages (MDM) and on the homeostasis of this important cellular reservoir. Materials and Methods: Replication (measured by p24 production) of the CCR5-tropic 81A strain increased up to 10 days post-infection and then reached a plateau. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 98 publications
(116 reference statements)
1
19
0
Order By: Relevance
“…CD4 + T cells are susceptible to cell death induced by CXCR4 and CCR5 using viral strains and MDMs infected by CCR5-using viruses show weak autophagy activation and increased viral replication compared to MDMs infected with viral strains that use CXCR4 (Espert et al, 2009). This is consistent with the fact that CCR5-tropic viral strains are more infectious than CXCX4-tropic viral strains in MDMs (Schweighardt et al, 2004;Willey et al, 2005;Petrov et al, 2013;Wang et al, 2015;Bolduc et al, 2017;Quitadamo et al, 2018;Borrajo et al, 2019), and with the in vivo prevalence of viruses that utilize CCR5 in the majority of infected individuals (De Jong et al, 1992;Roos et al, 1992;Schuitemaker et al, 1992;Connor et al, 1993;Zhu et al, 1993;van't Wout et al, 1994;Cornelissen et al, 1995;Spijkerman et al, 1995;Huang et al, 1996;Reece et al, 1998;Keele and Derdeyn, 2009;Salazar-Gonzalez et al, 2009). Likewise, functional CCR5 reduced the expression of autophagy genes, such as BECN1, ATG5 and microtubule associated protein 1 light chain 3 (LC3) alpha (MAP1LC3A), and promoted inflammation in an experimental asthmatic mouse model (Liu et al, 2021).…”
Section: Introduction a General Overview Of Hiv: Factors Related To Tsupporting
confidence: 74%
“…CD4 + T cells are susceptible to cell death induced by CXCR4 and CCR5 using viral strains and MDMs infected by CCR5-using viruses show weak autophagy activation and increased viral replication compared to MDMs infected with viral strains that use CXCR4 (Espert et al, 2009). This is consistent with the fact that CCR5-tropic viral strains are more infectious than CXCX4-tropic viral strains in MDMs (Schweighardt et al, 2004;Willey et al, 2005;Petrov et al, 2013;Wang et al, 2015;Bolduc et al, 2017;Quitadamo et al, 2018;Borrajo et al, 2019), and with the in vivo prevalence of viruses that utilize CCR5 in the majority of infected individuals (De Jong et al, 1992;Roos et al, 1992;Schuitemaker et al, 1992;Connor et al, 1993;Zhu et al, 1993;van't Wout et al, 1994;Cornelissen et al, 1995;Spijkerman et al, 1995;Huang et al, 1996;Reece et al, 1998;Keele and Derdeyn, 2009;Salazar-Gonzalez et al, 2009). Likewise, functional CCR5 reduced the expression of autophagy genes, such as BECN1, ATG5 and microtubule associated protein 1 light chain 3 (LC3) alpha (MAP1LC3A), and promoted inflammation in an experimental asthmatic mouse model (Liu et al, 2021).…”
Section: Introduction a General Overview Of Hiv: Factors Related To Tsupporting
confidence: 74%
“…In addition, with a novel microfluidic assay, we demonstrated that the THP-1 and MOLT-4 cells migrated further toward the supernatants of the TILRR-overexpressed HeLa cells. THP-1 cells (monocytes) and MOLT-4 cells (T cells) are CD4-expressing cells, the targets of HIV-1 (Berger et al, 1998;Verani et al, 1998;Borrajo et al, 2019). Thus, the supernatants of TILRR-overexpressed HeLa cells, containing multiple pro-inflammatory cytokines (Kashem et al, 2019), attracts HIV-1 target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, like CD4+ T cells, express CD4 and chemokine coreceptors CCR5 and CXCR4 on their cell surface allowing for HIV-1 susceptibility. Macrophages are susceptible to CCR5-tropic and dual-tropic viral infection, but determinants that assist in tropism are much more complicated than coreceptor usage ( Borrajo et al, 2019 ). Specifically, macrophages express significantly lower levels of CD4, meaning macrophage-tropic viruses must have a high degree of affinity to CD4 to mediate fusion with the macrophage cell membrane ( Kazazi et al, 1989 ; Joseph et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%